Rutting and Fatigue Cracking Resistance of Waste Cooking Oil (WCO) Modified Trinidad Asphaltic Materials - Rean Maharaj; Vitra Ramjattan-Harry; Nazim Mohamed (New Ideas Concerning Science and Technology Vol. 4, 2021)
The issue of the disposal of waste cooking oil (WCO), a product of the frying and cooking activities at high temperatures generated mainly from the food industry, restaurants, hotels and residences has become a major environmental issue. The influence of waste cooking oil (WCO) on the performance characteristics of asphaltic materials indigenous to Trinidad namely Trinidad Lake Asphalt (TLA), Trinidad Petroleum Bitumen (TPB) and a TLA:TPB (50:50) blend was investigated to deduce the applicability of the WCO as a performance enhancer for the base asphalt. The specific performance attributes of rutting resistance and fatigue cracking resistance as measured by the rheological properties of complex modulus (G*) and phase angle (?) were investigated. The results demonstrated that the incremental addition of WCO to the three parent binders resulted in an incremental decrease in the rutting resistance (decrease in G*/sin? values). However the incremental addition of WCO in the three asphaltic binders resulted in an increase in the fatigue cracking resistance (decrease G*sin? value). The fatigue cracking resistance and rutting resistance (G*sin? and G*/sin? respectively) for the TLA:TPB (50:50) blends were between those of the blends containing TLA and TPB as the base binder. An increase in temperature resulted in decreases in the values of G*sin? and G*/sin? for the three asphaltic parent binders and all of the WCO modified asphaltic blends indicating an increase in the resistance to fatigue cracking and a decrease in the rutting resistance with temperature. This study demonstrated the capability to create customized asphalt-WCO blends to suit special applications and highlights the potential for WCO to be used as an environmentally attractive option for improving the use of Trinidad asphaltic materials such as TLA and TPB.